2016
DOI: 10.21037/jtd.2016.03.54
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of ectopic adrenocorticotropic hormone syndrome with intra-thoracic tumor

Abstract: The thoracic cavity should be a focus in routine examinations of patients with symptoms of Cushing's syndrome (CS), because ectopic ACTH-producing tumors are commonly found in bronchus/lung and mediastinum. Despite the incidence of the pulmonary nodule secondary to opportunistic infection in some cases, surgery is still the first choice if the tumor is localized. The surgical procedure should be performed according to the principles in resection of lung cancer and mediastinal tumor. The surgical efficacy is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
5
1
4
Order By: Relevance
“…With reference to ectopic tumors, our study found 69% remission rate, comparable to the findings described in the literature, where cure rates vary greatly, ranging from 12 to 71%, in view of the various tumor types that can be the culprits thereof 24 .…”
Section: Discussionsupporting
confidence: 89%
“…With reference to ectopic tumors, our study found 69% remission rate, comparable to the findings described in the literature, where cure rates vary greatly, ranging from 12 to 71%, in view of the various tumor types that can be the culprits thereof 24 .…”
Section: Discussionsupporting
confidence: 89%
“…Ectopic ACTH-producing thymic carcinoid tumor is an extremely rare clinical condition, comprising 29% of all thymic carcinoids and 5–42% of all ectopic ACTH-producing syndrome [ 1 , 2 ]. It has been reported that radical surgical resection of the ACTH source is the only effective treatment [ 3 ]. Prior to surgery, medication therapy should be done to prevent perioperative complications and perform surgery when hormone values and symptoms are controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the management of EAS, surgical excision is the first treatment of choice once a single source of the ectopic tumor is successfully localized. Approximately 83% of EAS patients with bronchial carcinoid tumors recover after radical excision ( 4 , 11 ). If curative resection is not successful, medications including adrenal enzyme inhibitors and glucocorticoid antagonists should be considered to control the deleterious consequences of hypercortisolemia ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…If curative resection is not successful, medications including adrenal enzyme inhibitors and glucocorticoid antagonists should be considered to control the deleterious consequences of hypercortisolemia ( 11 ). Furthermore, a bilateral adrenalectomy with steroid replacement is an alternative treatment when the primary tumor cannot be found and medicinal controls fail ( 4 ). Fortunately, our patient endured hypercortisolism with the only necessary treatment being successful surgical resection of the source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation